On admissible total orders for typical hesitant fuzzy consensus measures. Issue 1 (13th September 2021) - Matzenauer, Monica; Santos, Hélida; Bedregal, Benjamín; Bustince, Humberto; Reiser, Renata
Abstract: In this paper, we discussconsensus measures for typical hesitant fuzzy elements (THFE), which are the finite and nonempty fuzzy membership degrees under the scope of typical hesitant fuzzy sets (THFS). In our approach, we present a model that formally constructs consensus measures by means of aggregations functions, fuzzy implication‐like functions and fuzzy negations, using admissible orders to compare the THFE, and also providing an analysis of consistency on them. Our theoretical results are applied into a problem of decision making with multicriteria illustrating our methodology to achieve consensus in a group of experts working with THFS.